Analisis Artefak Besi dari Beberapa Daerah di Indonesia - Sudarti Prijono (Balai Arkeologi Yogyakarta, 1994)
Metal artifacts from the past are discovered scattered in several regions in Indonesia. This shows that people in some of these areas are familiar with metal and may also know how to process it. Iron artifacts, both in the form of crusts and tool fragments, are remnants of past technology that are interesting to study in more depth.